On-Demand Hybrid Routing for Cognitive Radio Ad-Hoc Network - Zareei, M.; Mohamed, E.M.; Anisi, M.H.; Rosales, C.V.; Tsukamoto, K.; Khan, M.K. (Institute of Electrical and Electronics Engineers, 2016)
A novel on-demand cluster-based hybrid routing protocol for cognitive radio ad hoc network with non-uniform node distribution is proposed in this paper. At first, a novel spectrum-aware clustering mechanism is introduced. The proposed clustering mechanism divides node into clusters based on three values: spectrum availability, power level of node, and node stability. Therefore, clusters are formed with the highest stability to avoid frequent reclustering. Later, a routing algorithm is introduced to minimize the delay while achieving acceptable delivery ratio. In this paper, routing is defined as a multi-objective optimization problem to combine different individual routing metrics to form a global metric. Simulation results show that our proposed routing algorithm can guarantee a lower delay and a higher packet delivery ratio than conventional routing protocols for cognitive radio ad hoc networks. Due to our routing design specification, such as power consideration and low delay, it can be suitable to be adopted for Internet of Things applications.